Pendidikan multikultural untuk membangun bangsa yang nasionalis religius - Ambarudin, R. Ibnu (Universitas Negeri Yogyakarta, 2016)
Indonesia is a multicultural country, multiethnic, multi-religious, and multi other things spreaded in the world. Therefore, it needs a wise, appropriate, and effective ways to respond so that the steps taken are not slipped ways and consequently endanger the sustainability of the nation in the future. Multicultural education is required by Indonesia to reduce the occurrence of horizontal conflicts between communities, because of differences in culture, ethnicity, customs, and religion is the emphasizing on learning to appreciate differences and not be regarded as causes of fragmentation. This can be done through selection of suitable material or nuanced tolerance towards all humans in the frame of together and do not emphasize the difference because of the spirit of ideology or their respective groups. Conceptually many religions and beliefs in the shades of multicultural are expected to bring about harmonious relationship, but in the implementation phase are still a lot of gaps between the expectation and realization due to some exclusive-uninded people still in multicultural society.